Features of prevention of deviant behavior of students by means of sports and recreational activities - Irkhin, V.N.; Sazonov, D.N.; Sylka, S.I.; Voronin, I.Yu. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to revealing the features of the prevention of deviant behavior of students in a professional educational organization and university students by means of sports and recreational activities. Methods and structure of the study. The work used a multilevel personality questionnaire "Adaptiveness" (MPQ) (A.G. Maklakov and S.V. Chermyanin), the Spielberger-Khanin test; a questionnaire by A. Bass and A. Darki to determine the index of aggressiveness or hostility; monitoring the activities of teachers and students, questioning, pedagogical ex- periment, methods of mathematical processing of the results of the study. The survey involved 475 students in professional educational organizations and 2145 first-year students of Belgorod State National Research University; in the experiment - 90 students in professional educational organizations and 90 students of Belgorod State National Research University Results and conclusions. The results of the study showed the necessity and effectiveness of the use of means of physical culture and recreational activities in the prevention of students' deviant behavior. In the process of use of means of physical culture and recreational activities, attention was focused on getting pleasure from students in order to interrupt their destructive and stereotypical behavioral behavior programs, for which all forms of physical exercises were used aimed at emotionally active rest, entertainment, getting satisfaction from motor activity and comfortable psycho-emotional envi- ronment in the classroom.